Communication policy and its impact on bank development - Chang Yue (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the processes of marketing communications and their influence on the performance of banks in the competitive financial market. The subject of research includes theoretical provisions and practical aspects of the development and use of communication policies as a key tool for bank growth and development. The purpose of the master's thesis is to provide a theoretical foundation and develop methodological approaches and practical recommendations for improving the bank's communication policy and increasing its effectiveness. Tasks of a qualifying master's thesis include: to identify the tools and processes involved in organizing a bank's marketing communication policy; to examine the features of planning a bank's communication policy; to provide the technical and economic characteristics of JSC "UKRSIBBANK"; to analyze the current state of the communication policy at JSC "UKRSIBBANK"; to conduct a competitive analysis of the communication policy of JSC "UKRSIBBANK"; to justify the formation of an optimal set of marketing channels for the bank's communications; to propose organizational and methodological principles for building an effective marketing communication plan for banking practices, using JSC "UKRSIBBANK" as an example; to improve the organizational and information support for the bank's digital marketing communications. Based on the results of the research, theoretical and practical provisions were developed, leading to specific proposals for improving the communication policy of Ukrainian banks. Practical significance: The obtained results can be used to develop methodological frameworks for enhancing the communication policies of banks, ensuring alignment with modern conditions and competitive challenges in the financial market. The research findings are particularly relevant for JSC "UKRSIBBANK" and can be adapted by other banks to strengthen their marketing communication strategies, improve customer relationships, and achieve sustainable growth.
Scientific advisor: Malafeiev T., PhD in public administration, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; сommunication policy; elements of marketing communications; development of the company; increasing the efficiency of activities